2022
DOI: 10.1002/hep.32231
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and prediction of HBsAg seroclearance in a prospective multi‐ethnic HBeAg‐negative chronic hepatitis B cohort

Abstract: Background and Aims: Achieving HBsAg loss is an important landmark in the natural history of chronic hepatitis B (CHB). A more personalized approach to prediction of HBsAg loss is relevant in counseling patients. This study sought to develop and validate a prediction model for HBsAg loss based on quantitative HBsAg levels (qHBsAg) and other baseline characteristics.Methods: The Hepatitis B Research Network (HBRN) is a prospective cohort including 1240 untreated HBeAg-negative patients (1150 adults, 90 children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 27 publications
3
14
0
Order By: Relevance
“…As previously described, lower HBsAg levels were found in older HBeAgNeg patients [ 26 ]. Low levels of serum HBsAg (log ≤ 3 IU/mL) have been proposed to predict future HBsAg seroconversion [ 27 ].…”
Section: Discussionsupporting
confidence: 58%
“…As previously described, lower HBsAg levels were found in older HBeAgNeg patients [ 26 ]. Low levels of serum HBsAg (log ≤ 3 IU/mL) have been proposed to predict future HBsAg seroconversion [ 27 ].…”
Section: Discussionsupporting
confidence: 58%
“…HBeAg and HBsAg loss are important milestones in the course of CHB, associated with improved clinical outcomes. Factors associated with spontaneous HBeAg and HBsAg loss include older age, male sex, higher ALT level, HBeAg positivity, HBV genotype A or B, lower HBV DNA, and lower HBsAg levels 25–29 . We showed that a combination of host factors (age, sex, race/ethnicity), ALT, HBV DNA, and the use of antiviral therapy were highly predictive of HBeAg loss and HBsAg loss, respectively, with AUCs > 0.9.…”
Section: Discussionmentioning
confidence: 76%
“…Factors associated with spontaneous HBeAg and HBsAg loss include older age, male sex, higher ALT level, HBeAg positivity, HBV genotype A or B, lower HBV DNA, and lower HBsAg levels. [25][26][27][28][29] We showed that a combination of host factors (age, sex, race/ethnicity), ALT, HBV DNA, and the use of antiviral therapy were highly predictive of HBeAg loss and HBsAg loss, respectively, with AUCs > 0.9. Although in unadjusted analyses, the use of antiviral therapy was associated with a higher likelihood of HBeAg and HBsAg loss, respectively; once each model controlled for HBV DNA, the direction of the association with antiviral therapy changed, likely due to the impact of antiviral therapy on HBV DNA.…”
Section: Discussionmentioning
confidence: 95%
“…HBsAg seroclearance was also found to be highly associated with older age, nonasian race, inactive HBsAg carrier, HBV genotype A, lower HBV DNA, and quantitative HBsAg levels. 29 NAs suppress HBV DNA rather than directly acting on cc-cDNA. Consequently, it is very difficult for NAs to prevent the production of HBV particles and their antigens.…”
Section: Patterns and Epidemiology Of Continuous Hbsag Seroclearancementioning
confidence: 99%